Feline leishmaniosis: hematological and biochemical analysis - da Silva, Diogo Tiago; Alves, Maria Luana; Spada, Júlio Cesar Pereira; Leonel, João Augusto Franco; Vioti, Geovanna; Benassi, Julia Cristina; Carregaro, Valéria Maria Lara; Alves-Martin, Maria Fernanda [UNESP]; Starke-Buzetti, Wilma Aparecida [UNESP]; de Sousa Oliveira, Trícia Maria Ferreira (FapUNIFESP (SciELO), 2023)
One hundred and sixty-six cats from two animal shelters were subjected to enzyme-linked immunosorbent assay (ELISA), indirect immunofluorescence antibody test (IFAT), conventional polymerase chain reaction (cPCR), quantitative PCR (qPCR) and parasitological tests (PA) for the diagnosis of Leishmania spp. Among them, 15% (25/166), 53.6% (89/166), 3.6% (06/166) and 1.8% (03/166) were positive by ELISA, IFAT, both PCRs and PA, respectively. The sequencing of ITS-1 PCR amplicons revealed a 100% match with Leishmania infantum. After the Leishmania spp. survey, 12 cats were selected and divided into two groups for clinical, hematological, and biochemical analysis: six L. infantum positive cats (G1) and six Leishmania spp. negative cats (G2). All the cats were negative for feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV). A statistical analysis indicated significantly low platelet counts and significant hyperproteinemia associated with hypoalbuminemia in positive cats (p<0.05). Our results suggest that in endemic areas, cats with clinical signs of feline leishmaniosis (such as skin lesions, weight loss and/or enlarged lymph nodes) and that exhibit hematological and biochemical changes, such as low platelet counts and hyperproteinemia with hypoalbuminemia, should be tested for Leishmania spp. infection.
Leishmaniose felina: análises de hematologia e bioquímica
Keywords: Cats; hyperproteinemia; hypoalbuminemia; Leishmania infantum; thrombocytopenia